2017
DOI: 10.14202/vetworld.2017.1118-1128
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and zoonotic impact of Shiga toxin producing Escherichia coli in some wild bird species

Abstract: Aim:Wild birds are considered silent vectors of some zoonotic water and food borne pathogens of public health significance. Owing to the importance of Shiga toxin producing Escherichia coli (STEC) as the most pathogenic among the emerging diarrheagenic E. coli groups that can infect man; the present study was designed to detect the occurrence of STEC among wild birds in Egypt.Materials and Methods:A total of 177 intestinal content swab samples originating from five wild bird species were investigated for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Shiga toxin-producing E. coli have been largely detected in domestic and wild animals, including gulls [ 7 , 14 ]. Although the prevalence was lower, as compared to other surveys conducted on gulls across Europe [ 12 ], the STEC percentage is in line with other studies conducted on wild birds recovered in urban surroundings [ 34 , 35 ]. Unfortunately, it was not possible to establish the O:H serotypes, in order to determine the seropathotypes according to Karmali et al [ 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…Shiga toxin-producing E. coli have been largely detected in domestic and wild animals, including gulls [ 7 , 14 ]. Although the prevalence was lower, as compared to other surveys conducted on gulls across Europe [ 12 ], the STEC percentage is in line with other studies conducted on wild birds recovered in urban surroundings [ 34 , 35 ]. Unfortunately, it was not possible to establish the O:H serotypes, in order to determine the seropathotypes according to Karmali et al [ 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…The occurrence among the examined ducks was 0.48%, while STEC was detected only among Anas crecca duck species with an occurrence rate 0.92%, with such result was lower than that obtained by Fadel et al . in Egypt, who isolated STEC with occurrence rate 10% (1/10) among the examined Anas crecca [ 30 ] and Bertelloni et al . in Italy, who recovered STEC with occurrence rate 4.5% (1/22) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] while Fadel et al . [ 30 ] found both stx1 and stx2 genes in only one positive duck sample. On the other hand, the occurrence of STEC among the examined migratory quails was 0.71%, which is considered lower than that found by Dipineto et al .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that birds can harbor STEC, but, like cattle, they seem refractory to Stx and could be a spillover host. Starlings and pigeons would be likely culprits in a spillover scenario because these two avian species can inhabit city buildings, parks and playgrounds, where humans may be exposed to these animals and their feces [ 28 , 29 , 30 ]. Wild birds were first identified as a potential source of STEC infection in 1997 [ 31 ].…”
Section: Discussionmentioning
confidence: 99%